INTEGRASI MADRASAH DIGITAL UNTUK PRESENSI DAN DAFTAR NILAI PADA MTSS YP AL AZHAR - Abri Pratama; Sri Wahyuni; Randi Rian Putra (Jurnal Nasional Teknologi Komputer, 2025)
The development of information and communication technology (ICT) has penetrated various aspects of life, including the world of education. The integration of digital madrasah in the attendance system and grade management at MTsS YP Al Azhar. The research method used is a qualitative approach with a case study, involving observation, interviews, and literature study as data collection techniques. The results showed that the implementation of the digital system has improved the efficiency of the attendance process and management of student grades, facilitated access to information for teachers and parents, and reduced the use of paper. However, there are obstacles such as limited training for educators and technology infrastructure that has not been optimized. The conclusion of this study is that the integration of digital technology at MTsS YP Al Azhar has a positive impact on education management, although further efforts are needed in increasing the capacity of human resources and providing supporting infrastructure.